2021
DOI: 10.4103/ijo.ijo_3062_20
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the association of intronic single nucleotide polymorphisms of crystallin gene family with congenital cataract

Abstract: Purpose: Introns play an important role in gene regulation and expression. Single nucleotide polymorphisms (SNPs) in introns have the potential to cause disease and alter the genotype–phenotype association. Hence, this study aimed to decipher the association of SNPs in the introns of the crystallin gene in congenital cataracts. Methods: SNPs in the introns of crystallin gene family – CRYAA (rs3788059), CRYAB (rs20708… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The functional role of the genomic region strongly determines the localization of polymorphisms, since SNPs in exons have a potential impact on gene products that on a further scope may be the cause of a disease or may alter quantitative phenotypes (15). Since introns exhibit various regulatory roles, the presence of polymorphism in introns may indirectly impact gene products or their expression levels (16).…”
Section: Discussionmentioning
confidence: 99%
“…The functional role of the genomic region strongly determines the localization of polymorphisms, since SNPs in exons have a potential impact on gene products that on a further scope may be the cause of a disease or may alter quantitative phenotypes (15). Since introns exhibit various regulatory roles, the presence of polymorphism in introns may indirectly impact gene products or their expression levels (16).…”
Section: Discussionmentioning
confidence: 99%
“…SNPs in intronic regions might cause diseases and alter the genotype-phenotype association by generating splice variants of transcripts and promoting or disrupting the binding and function of long noncoding RNAs (lncRNAs) (such as rs3731864 G/A and rs3731865 G/C). SNPs in the 5′-UTR regions can potentially affect translation, whereas those in the 3′-UTR region (i.e., rs17235416 + TGTG/−TGTG) impact the binding of microRNAs (miRNAs) 65,66 . Intronic sequences might be conserved, as they contain expression-regulating elements that impose functional constraints on their evolution 67,68 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that introns were involved in the gene splicing in eukaryotes, and that the mutation of introns might change the splicing efficiency, which resulted in the change of amino acid coding and eventually affected the biological traits [ 38 , 39 ]. Even if the intron mutation has no effect on the amino acid sequence, it may also result in the inactivation of the splicing site, or it may contain enhancer sequences to promote the specific transcription of the gene, affecting the animal phenotype [ 40 , 41 ]. The correlation between the SNPs on the introns and the milk fat traits of cattleyak may have a causal mutation, or it may be that these five SNPs are closely related to the SNPs on the exons.…”
Section: Discussionmentioning
confidence: 99%